Interference to Telephone Lines - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2017)
A paper from 1936 exploring the effects of electrification of country Tasmania and the increasing interference to telecommunication circuits by high voltage power lines installed in close proximity.